Building Sustainable Family Businesses - KOH, Annie (Institutional Knowledge at Singapore Management University, 2013)
In 2012, the Singapore Management University (SMU) established Southeast Asia’s first regional institute to specifically serve the needs of business families in this part of the world. The Business Families Institute at SMU, or BFI@SMU, helmed by its Academic Director, Associate Professor Annie Koh, focuses on addressing the educational, engagement and research needs of Asian business families. It aims to help them deal with business family-specific issues such as family ownership, business succession, business diversification and governance. Associate Professor Annie Koh, who is also SMU’s Vice President for Business Development and External Relations, and an Associate Professor of Finance at SMU’s Lee Kong Chian School of Business, has been involved in various research projects relating to family businesses. In this podcast, she shares her insights and knowledge about family businesses, the opportunities and challenges facing family businesses in Asia, and the factors that contribute to their success in the long-run.